EARLY DETECTION OF TRICHOGRAMMA CHILONIS SEXES USING THE EGG COLOR AND SIZE OF ITS FACTITIOUS HOST, CORCYRA CEPHALONICA - F.X. Susilo, Desta S. Romli, Sunaryo, and M. Solikhin . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2007)
Early Detection of Trichogramma chilonis sexes using the egg color and size of its factitious host Corcyra cephalonica. This study was aimed to detect the sexes of Trichogramma chilonis Ishii (Hymenoptera: Trichogrammatidae) prior to their emergence using the egg color and size of their factitious host, Corcyra cephalonica (Lepidoptera: Pyralidae). A gray scale of 1 – 7 was used to rank the egg color while a micrometer was used to observe the egg size under a dissecting microscope. Ten of newly laid C. cephalonica eggs were glued in two rows (0.5 cm x 0.4 cm distance) on a piece of oviposition paper. Five replications of such batches were exposed in a test tube to a gravid T. chilonis female for 24 hours under 100 watts of illumination. Following the withdrawal from the oviposition arena the eggs were each observed daily for their color and size and the sex of the emerged T. chilonis progeny was documented. Binomial Z-test at 0.05 level of significance was used to validate the predicted proportion of T. chilonis sexes from five batches of 50 parasitized C. cephalonica eggs. The results showed as predicted that more T. chilonis female progeny emerged from light-colored C. cephalonica eggs (scale 2 – 5) following oviposition by parent parasitoid or from larger C. cephalonica eggs (> 500 µm).